Economic Impacts of Business Continuity on an Outbreak of Highly Pathogenic Avian Influenza in Minnesota Egg Laying Operations. (20th February 2019) - Thompson, Jada M.; Pendell, Dustin L.; Boyer, Tim; Patyk, Kelly A.; Malladi, Sasidhar; Weaver, J. Todd
Abstract: Animal disease outbreaks can cause disruptions in domestic and international markets. Business continuity aims to provide a proactive approach to alleviate some of these negative effects on consumers, producers, and agribusinesses. Using a partial equilibrium model of the U.S. egg industry, the economic impacts of business continuity during an epidemiological simulated disease event are modeled. Results show total welfare losses can be reduced by allowing permitted movement during an outbreak given a specified level of biosecurity. Understanding the potential market responses business continuity can have on the market may lead to reductions in the negative implications of a disease event.